Uji Validitas Media Pembelajaran PPT Interaktif Berbasis Genially pada Materi Bioteknologi Konvensional untuk Peserta Didik kelas IX SMP: The Validity of Genially-Based Interactive PowerPoint Presentations on Conventional Biotechnology Content for Ninth-Grade Junior High School Students - Disya Illona Zalikhah Widad; Siti Mulyani; Elsa Rahmawati; Zahra Salfadila; Nofita Fajariyanti; Lukman Nulhakim; Annisa Novianti Taufik (Sumule Indonesia Publishing, 2026)
This study aims to determine the validity of an interactive Genially-based PowerPoint (PPT) learning medium on conventional biotechnology for ninth-grade junior high school students. The study employed the Research and Development (R&D) method using the Borg and Gall model, limited to the product validation stage. Validation was conducted by two expert validators with expertise in ICT-based learning media using a 1–4 Likert-scale questionnaire with 20 indicators, including content appropriateness, media presentation, interactivity, ease of use, accessibility, media innovation, and language use. Data were analyzed descriptively and quantitatively by calculating the validity percentage and qualitatively by reviewing the validators’ comments and suggestions. The validation results showed that the media achieved a validity percentage of 90,00 %, falling into the “highly valid” category. Thus, the Genially-based interactive PowerPoint presentation was deemed suitable, based on the validators’ assessment, as a science learning medium for the topic of Conventional Biotechnology.